2020
DOI: 10.1007/s00253-020-10385-6
|View full text |Cite|
|
Sign up to set email alerts
|

A new Rhodococcus aetherivorans strain isolated from lubricant-contaminated soil as a prospective phenol-biodegrading agent

Abstract: Microbe-based decontamination of phenol-polluted environments has significant advantages over physical and chemical approaches by being relatively cheaper and ensuring complete phenol degradation. There is a need to search for commercially prospective bacterial strains that are resistant to phenol and other co-pollutants, e.g. oil hydrocarbons, in contaminated environments, and able to carry out efficient phenol biodegradation at a variable range of concentrations. This research characterizes the phenol-biodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Among the members of this genus, R. aetherivorans is a species of special interest in the biodegradation of various resistant to degradation pollutants, such as noncyclic and cyclic ethers [18][19][20], aliphatic and aromatic hydrocarbons [21] and chlorinated organic compounds [22]. Our previous studies have shown that R. aetherivorans UCM Ac-602 strain efficiently degraded phenol as well as n-hexadecane, kerosene, diesel fuel and transformer oil [7]. It is known that changes in the lipid composition of cells, primarily fatty acids, are of great importance in the adaptation of microorganisms to the assimilation of membraneactive compounds, in particular phenol and its derivatives [3,8,9,11].…”
Section: Discussion Actinobacteria Of the Genusmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the members of this genus, R. aetherivorans is a species of special interest in the biodegradation of various resistant to degradation pollutants, such as noncyclic and cyclic ethers [18][19][20], aliphatic and aromatic hydrocarbons [21] and chlorinated organic compounds [22]. Our previous studies have shown that R. aetherivorans UCM Ac-602 strain efficiently degraded phenol as well as n-hexadecane, kerosene, diesel fuel and transformer oil [7]. It is known that changes in the lipid composition of cells, primarily fatty acids, are of great importance in the adaptation of microorganisms to the assimilation of membraneactive compounds, in particular phenol and its derivatives [3,8,9,11].…”
Section: Discussion Actinobacteria Of the Genusmentioning
confidence: 99%
“…To assess the effect of phenol on fatty acid composition of R. aetherivorans UCM Ас-602 compared to that on n-hexadecane or glucose, the fatty acid profiles of cells were compared in cultures reaching the stationary growth phase at cultivation on these substrates. In previous studies, we have shown that R. aetherivorans UCM Ас-602 cells grown at a phenol concentration of 0.75, 1.0 and 1.5 g/L as a sole carbon and energy source reached the stationary growth phase and completely degraded phenol after 24, 48 and 72 h respectively [7]. Samples of control cells grown on the same medium with n-hexadecane and glucose were taken after 72 and 24 hours, respectively, until the cultures reached the stationary growth phase.…”
Section: Effects Of Phenol On Fatty Acid Composition Of R Aetherivorans Ucm ас-602 In Comparison To Glucose or N-hexadecanementioning
confidence: 95%
See 2 more Smart Citations
“…Due to its high toxicity to life and overall chemical stability, phenol frequently causes the breakdown of wastewater treatment plants [ 2 , 3 ]. Thus, phenol has been listed as one of 126 priority pollutants by the US Environmental Protection Agency [ 4 ]; the maximum phenol content in drinking water should be below 1.0 μg/L [ 5 ].…”
Section: Introductionmentioning
confidence: 99%